Las enmiendas o proposiciones de ley que afectan al acceso al mercado (Directiva Servicios, 2006/123/CE): el cumplimiento de la obligación de notificación a la Comisión Europea (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2018)
Compulsory notification to the European Commission of amendments to rules related to Access to Markets is not foreseen by the Statutory Regulations and provoked changes in legislative proceedings.
Keywords: Amendments; Compulsory Notification; Services Directive; Legislative proceedings